Sistem Monitoring Tambak Pada Budidaya Udang Menggunakan Wireless Sensor Network Dan Internet Of Things (Studi Kasus: Tambak Desa Bratasena Mandiri) - Muhammad Nurul Huda; Agung Wijoyo (CV. Multi Kreasi Media, 2023)
With current technological advances and developments, the author needs to design pond water quality monitoring tools such as temperature, pH, and TDS (Total Dissolved Solid). Thus encouraging them to find new things to simplify and optimize the daily activities of pond farmers. This tool aims to ensure/determine the actual water quality, in this way it can determine actions to minimize disease in shrimp and reduce mortality in shrimp, the use of this tool can be done especially before entering shrimp seeds by checking the water first. to ensure water quality and produce water that is suitable for shrimp seedlings. Why is that, because immature shrimp seeds will be more sensitive to disease. From there the author of this thesis designed a pond water quality monitoring tool, by adding a feature that can control the water wheel. Because the water wheel is also useful for maintaining good water quality. From the test results, it was found that the system could read data from the temperature, Ph, and TDS sensors. The temperature sensor can read the temperature with an accuracy of 90%. The Ph sensor can read the acidity of water with an accuracy of 80%. The TDS sensor can read dissolved solids in water in ppm units and has an accuracy of 80%. The time used in reading each sensor data is every 5 seconds. In controlling the water wheel through the Blynk application, it can activate the DC motor as a prototype of the water wheel through a relay at a certain distance.